Determination of Beta-carotene in tiessa (Pouteria campechiana (HBK.) Baehni) flour using thin layer chromatography - Yu, Frances L.
Four batches of approximately 20 Kg of firm, ripe tiessa (pouteria campechiana (HBK) Baehni) was made into flour by the following process: washing, grating, drying for 15 hours, milling, sifting, and packaging. The final product with an average moisture content of 4.37%, gave a yield for production of 23.23%. The flour caked easily, and was characterized as being highly hygroscopic and non-free flowing. This was evidenced by a moisture gain of 12% upon exposure to air for 6 1/2 hours at ambient conditions. Beta-carotene was analyzed using thin layer chromatography, and the absorbance of the extract was read at 451 nm. Results of the determination showed averages of 43.92 mcg and 57.42 mcg per gram of edible portion of raw fruit and untreated flour, respectively.